Fatores influenciadores da inovação em bibliotecas públicas acadêmicas - Cruz, Keila Fernanda de Souza (Universidade Federal de São Carlos, 2019)
Towards the academic libraries to remain relevant to their users and to fulfill their role as information centers in universities, they need to innovate to create services that meet these needs. Innovation enables libraries to create new services or enhance existing services for their user communities. However, innovation is a complex process and several factors can influence or inhibit the innovation process in libraries. This paper aims to characterize the innovations developed by academic libraries (belonging to federal and state universities in Brazil) and the factors that influence them. Thus, it seeks to identify the antecedent and consequent factors of library innovation. To achieve the objectives, the survey research was adopted. Therefore, it is a research with quantitative approach. The execution was performed in three stages: i) the bibliographic research for the theoretical foundation about the process of innovation in services and innovation in libraries; ii) the survey for data collection and iii) data treatment and analysis. For data collection, an electronic questionnaire was sent by email to the library directors of 98 public universities (63 federal and 35 state). At the end, we obtained a sample composed of 151 respondents. For data analysis, two approaches were used. The first was based on descriptive statistics, while the second corresponded to the application of the Structural Equation Modeling technique. The results made it possible to characterize the innovations developed by the libraries. Despite the creation of innovative services, most libraries implement minor adaptations and improved versions of existing services, indicating the predominance of incremental innovations. As for influencing factors, Leadership, Culture and Climate, and Role of Servers and Co-creation are important antecedents and innovation in libraries. On the other hand, factors such as process and resources have less influence. The results also indicate that co-creation, especially of frontline servers, is an important predictor of innovation. Library managers can use research findings to increase the effectiveness of innovation processes. As a consequence, the results indicate the contribution of innovations in improving the image and satisfaction of library users. Finally, limitations and perspectives for future work are presented at the end of this research
Influencing factors of innovation in academic public libraries
Keywords: Inovação; Inovação em serviços; Cocriação; Biblioteca acadêmica; Innovation; Innovation in services; Co-creation; Academic library; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO PUBLICA::ORGANIZACOES PUBLICAS; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA